2021
DOI: 10.1088/1572-9494/abf8a1
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer analysis of MHD rotating flow of Fe3O4 nanoparticles through a stretchable surface

Abstract: The flow of a magnetite-H2O nanofluid has been considered among two rotating surfaces, assuming porosity in the upper plate. Furthermore, the lower surface is considered to move with variable speed to induce the forced convection. Centripetal as well as Coriolis forces impacting on the rotating fluid are likewise taken into account. Adequate conversions are employed for the transformation of the governing partial-differential equations into a group of non-dimensional ordinary-differential formulas. Numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…They showed that carbon nanotube and Fe 3 O 4 -based nanocomposite exhibits effective heat transmission and thermal efficiency compared to single ferrite nanoparticles. Shahzad et al 41 investigated Fe 3 O 4 -H 2 O nanofluid behavior within two revolving disks considering the upper one as porous. They marked frictional amplification but heat transmission reduction for rotation.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that carbon nanotube and Fe 3 O 4 -based nanocomposite exhibits effective heat transmission and thermal efficiency compared to single ferrite nanoparticles. Shahzad et al 41 investigated Fe 3 O 4 -H 2 O nanofluid behavior within two revolving disks considering the upper one as porous. They marked frictional amplification but heat transmission reduction for rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the influence of the embedded constraints on hybrid-class nanofluid flow are discussed and designated that hybrid-class nanofluids are the best thermal-conductor and play significant role in the circulation of blood in human body. Shahzad et al [6] analyzed MHD rotating flow of Fe 3 O 4 tiny-particles through stretchable obstacle with the manifestation of heat transfer. Here, Coriolis as well as centripetal forces taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out that the ability of the fluid on the drag based both on the physical parameters and the geometry of the proposed system. Several important researches regarding the topic of nanoliquids flow and heat mass transfer have been reported [32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%